On the crystallography and reversibility of lithium electrodeposits at ultrahigh capacity - Zhao, Qing; Deng, Yue; Utomo, Nyalaliska W.; Zheng, Jingxu; Biswal, Prayag; Yin, Jiefu; Archer, Lynden A. (Nature communications, 2021)
Lithium metal is a promising anode for energy-dense batteries but is hindered by poor reversibility caused by continuous chemical and electrochemical degradation. Here we find that by increasing the Li plating capacity to high values ( e.g ., 10–50 mAh cm −2 ), Li deposits undergo a morphological transition to produce dense structures, composed of large grains with dominantly (110) Li crystallographic facets. The resultant Li metal electrodes manifest fast kinetics for lithium stripping/plating processes with higher exchange current density, but simultaneously exhibit elevated electrochemical stability towards the electrolyte. Detailed analysis of these findings reveal that parasitic electrochemical reactions are the major reason for poor Li reversibility, and that the degradation rate from parasitic electroreduction of electrolyte components is about an order of magnitude faster than from chemical reactions. The high-capacity Li electrodes provide a straightforward strategy for interrogating the solid electrolyte interphase (SEI) on Li —with unprecedented, high signal to noise. We find that an inorganic rich SEI is formed and is primarily concentrated around the edges of lithium particles. Our findings provide straightforward, but powerful approaches for enhancing the reversibility of Li and for fundamental studies of the interphases formed in liquid and solid-state electrolytes using readily accessible analytical tools. Lithium metal batteries offer high-capacity electrical energy storage but suffer from poor reversibility of the metal anode. Here, the authors report that at very high capacities, lithium deposits as dense structures with a preferred crystallite orientation, yielding highly reversible lithium anodes.